PENGARUH TATA KELOLA PERUSAHAAN DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN YANG DIMODERASI OLEH DIVIDEN DAN KINERJA KEUANGAN - Ulfa Khairunisa; Elvin Bastian; Dadan Ramdhani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of corporate governance and intellectualcapital on corporate value with dividend and financial performance as moderatingvariables. The population in this study consists of all companies listed in LQ45 inIndonesian Stock Exchange. Samples are selected by purposive sampling techniquewith certain criteria: companies listed in the LQ45 index between 2015 and 2019,companies that issued financial statements between 2015 and 2019, companies thatdistributed dividends between 2015 and 2019 and companies that apply theprinciples of corporate governance. This research used 215 companies. The datawere analyzed using the Moderated Regression Analysis (MRA) analysis technique.The result of this study shows that corporate governance and intellectual capital have positively significant influence on corporate value. In addtition, dividend andfinancial performance moderate the relationship of corporate governance andintellectual capital. But dividend did not moderate the relationship of corporategovernance and financial performance as well as the relationship of financialperformance with coporate governance and intellectual capital.